The Discovery of a Pseudo SNP and its Usage in Gender Test - Huang, MD, MPH, Jie (North American Journal of Medicine and Science, 2009)
Single Nucleotide Polymorphism (SNP) technology has been widely used in genome-wide association studies (GWAS). Quality control procedures usually includes testing minor allele frequency, hardy–weinberg equilibrium, call frequency, and concordance rate. However, little effort has been reported to validate a SNP itself. Here we report how a SNP is found not to be actual polymorphic at one locus, instead from two sequences on two different chromosomes. [N A J Med Sci. 2009;2(2):41.]